2022
DOI: 10.1093/ecco-jcc/jjac178
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Neutrophils for Predicting Relapse and Remission in Ulcerative Colitis

Abstract: Background and aims This study examines colonic histologic features in ulcerative colitis (UC) in endoscopic remission to determine which cell types and biopsy sites best predict a patient's likelihood of remaining in remission. Methods This is a retrospective chart, endoscopy and histology review of 166 persons with UC in endoscopic remission followed in a single IBD practice over a median of 6 years (range, 2-11 years). Cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Research has demonstrated that plasma cells play a pivotal role in UC-associated inflammatory infiltrates, and their expansion is associated with an increased risk of clinical relapse. 63,64 Restoring immune balance by inhibiting macrophage M1 polarization and promoting M2 polarization is a valuable therapeutic strategy for UC. 65 Neutrophil infiltration severity correlates with disease activity in UC and is incorporated into the scoring system for disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated that plasma cells play a pivotal role in UC-associated inflammatory infiltrates, and their expansion is associated with an increased risk of clinical relapse. 63,64 Restoring immune balance by inhibiting macrophage M1 polarization and promoting M2 polarization is a valuable therapeutic strategy for UC. 65 Neutrophil infiltration severity correlates with disease activity in UC and is incorporated into the scoring system for disease activity.…”
Section: Discussionmentioning
confidence: 99%